1978
DOI: 10.2355/tetsutohagane1955.64.5_595
|View full text |Cite
|
Sign up to set email alerts
|

α′→γ Reverse Transformation in an 18%Ni Maraging Steel

Abstract: Mechanism of ƒ¿'•¨ƒÁ reverse transformation has been examined by means of dilatometric measurements, X-ray analysis and structural observations in an 18% Ni maraging steel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…[1][2][3][4] A high Ni content decreases the T0 temperature in such steels (T 0 : temperature where the Gibbs free energies of martensite and austenite are equal), hence, suppressing diffusional transformation. It was further reported that the austenite formed by martensitic reversion (martensitically reversed austenite) is statically recrystallized by prolonged austenitization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] A high Ni content decreases the T0 temperature in such steels (T 0 : temperature where the Gibbs free energies of martensite and austenite are equal), hence, suppressing diffusional transformation. It was further reported that the austenite formed by martensitic reversion (martensitically reversed austenite) is statically recrystallized by prolonged austenitization.…”
Section: Introductionmentioning
confidence: 99%
“…This effect results in a considerable loss of strength and toughness after quenching, although the prior austenite grain size is markedly refined by the recrystallization. 2,4) In order to explain this phenomenon, it was suggested that martensitically reversed austenite contains a high dislocation density that may provide the driving force for primary recrystallization. It was suggested that the high dislocation density that is typical of maraging steel may contribute to the good mechanical property of this material class due to an ausforming-like effect as long as the recrystallization of the martensitically reversed austenite does not occur.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that martensitically reversed austenite is easy to recrystallize at elevated temperatures owing to a high dislocation density. [1][2][3][4][5]15) Therefore, it is thought that displacive reversed austenite statically recrystallizes in a short time resulting in the formation of fine austenite grains. These experimental results demonstrate that displacive reversion accompanied by carbon diffusion takes place even in low-alloyed steels when the heating rate is sufficient for suppressing diffusive reversion and also that the displacive-reversed austenite can easily recrystallize.…”
Section: Notementioning
confidence: 99%
“…It is known that the reversible transformation from martensite to austenite (martensitic reversion) occurs in maraging steel owing to its high Ni content. [1][2][3][4] Previously, 5) the authors of the current study directly observed an austenitic structure formed by martensitic reversion (martensitically reversed austenite) in 18%Ni-C (% = wt.%) steel. It was reported that after reheating the sample to a temperature above the martensitic austenite-start temperature, As, all martensite laths originally formed via an fcc→bcc martensitic transformation reverse into new austenite during the bcc→fcc martensitic reversion, thus returning to an original austenitic structure with the same crystallographic orientation.…”
mentioning
confidence: 99%
See 1 more Smart Citation